Amazon snowstorm in the jungle ; Rigging for the Amazon - Cousteau, Jacques-Yves; Welles, Orson, 1915- ([S.l.] : The Cousteau Society Inc. and TBS Productions, 1984)
The Snowstorm in the jungle shows Amazon Basin in South America is home to more species of animals, mysteries and more natural oddities than perhaps any other place on earth. This daring expedition led to the unexplored region and expose the source of cocaine
Rigging for the Amazon gives a fascinating glimpse at the monumental preparations for the Cousteaus formidable Amazon expedition and witnessing the rebuilding of the legendary Calypso for the Cousteaus' challenging adventure
Executive producers, Jacques-Yves Cousteau, Jean-Michel Cousteau
Narrated by Orson Welles
Title from data sheet
Keywords: Cocaine industry -- South America; Cocaine; Cocaine habit; Drug abuse